The vegetation of the cretaceous outcrops of Novhorod-Siverskyi Polesie loess “islands” (Ukraine) and the new locality of Gentiana cruciata L. - Lukash, Oleksandr; Miroshnyk, Iryna; Yakovenko, Oleksandr; Strilets, Svitlana (Ecological Questions, 2019)
The vegetation of the cretaceous outcrops of Novhorod-Siverskyi Polesie loess “islands” is represented by the grasslands communities of the Artemisietea vulgaris Lohmeyer et al. in Tx. ex von Rochow1951, Festuco-Brometea Br.-Bl. et Tx. ex Soó 1947, TrifolioGeranietea sanguinei T. Müller 1962 classes and shrubby phytocoenoses of the Robinietea Jurko ex Hadač et Sofron 1980 class. The structure and composition of the plant communities are influenced by the degree of anthropogenic influence (both in the past and present) on the ecosystems of cretaceous outcrops. The determining anthropogenic factors contributing to the formation of the ruderal communities were chalk mining and gardening. The influence of erosive processes is manifested in the spatial delimitation of plant communities of various syntaxonomic belongings. The anthropogenic successional communities: semiruderal grasslands and herblands of the immoral and subboreal zones of Europe (ConvolvuloAgropyretum repentis Felföldy (1942) 1943, Poo compressae-Tussilaginetum farfarae R. Tx. 1931) and scrub communities of temperate Europe, represented by the Elytrigio repentisRobinietum Smetana 2002 phytocoenoses typical for Steppe zones, prevail. Semixerothermic communities were found on the steep slopes of the cretaceous outcrops (eastern and southwestern expositions) – early successional stages with a significant amount of the characteristic species of the Festuco-Brometea Br.-Bl. et Tx. ex Soó 1947 class. On the cretaceous outcrops of Novhorod-Siverskyi Polesie loess “islands” the communities of Trifolion medii T. Müller 1962 (meso-subxerophytic fringe phytocoenoses on nutrient-poor but base-rich soils at lower altitudes of temperate Western and Central Europe) is localized on the slopes of the eastern and southeastern parts of the expositions which do not undergo anthropogenic influence and are separated by erosion forms. Such conditions were favorable for preserving the Gentiana cruciata L. relict species in this locality. The population of this species was found in the area of 50 m2 in the Trifolio medii-Agrimonietum Th. Müller 1962 association community and represented by two compact groups of individuals (the area of 0.5 m 2 each) and individual plants. In order to preserve the habitat of this rare species, it is worth creating here a reserve.